Wetlands serve as natural sources for improvement of stream ecosystem health in regions affected by acid deposition. (14th July 2013) - Pound, Katrina L.; Lawrence, Gregory B.; Passy, Sophia I.
Abstract For over 40 years, acid deposition has been recognized as a serious international environmental problem, but efforts to restore acidified streams and biota have had limited success. The need to better understand the effects of different sources of acidity on streams has become more pressing with the recent increases in surface water organic acids, or 'brownification, ' associated with climate change and decreased inorganic acid deposition. Here, we carried out a large scale multi‐seasonal investigation in the Adirondacks, one of the most acid‐impacted regions in the United States, to assess how acid stream producers respond to local and watershed influences and whether these influences can be used in acidification remediation. We explored the pathways of wetland control on aluminum chemistry and diatom taxonomic and functional composition. We demonstrate that streams with larger watershed wetlands have higher organic content, lower concentrations of acidic anions, and lower ratios of inorganic to organic monomeric aluminum, all beneficial for diatom biodiversity and guilds producing high biomass. Although brownification has been viewed as a form of pollution, our results indicate that it may be a stimulating force for biofilm producers with potentially positive consequences for higher trophic levels. Our research also reveals that the mechanism of watershed control of local stream diatom biodiversity through wetland export of organic matter is universal in running waters, operating not only in hard streams, as previously reported, but also in acid streams. Our findings that the negative impacts of acid deposition on Adirondack stream chemistry and biota can be mitigated by wetlands have important implications for biodiversity conservation and stream ecosystem management. Future acidification research should focus on the potential for wetlands to improve stream ecosystem health in acid‐impacted regions and their direct use in stream restoration, for example, through stream rechanneling or wetland construction in appropriate hydrologic settings.